Giant comprehensive energy storage performance in Pb-doped Bi0.25Na0.25Sr0.5TiO3 ceramics via multiscale regulation of grain size and relaxation behavior. Issue 4 (April 2023) - Guo, Jian; Fan, Xuhui; Zhang, Ji; Zhang, Shan-Tao; Yang, Bin
Abstract: Developed ceramic capacitors with excellent recoverable energy storage density ( W rec ) and efficiency ( η ) are greatly desired for next-generation pulsed power devices but challenge as well. Herein, outstanding W rec of 5.2 J/cm 3 and η of 82% are achieved in the PbO-doped fine grain Bi0.25 Na0.25 Sr0.5 TiO3 (BNST-P) based relaxor ferroelectric ceramics. The corresponding mechanism is that A-site Pb-doping increases maximum polarization and breakdown strength, and suppresses remnant polarization simultaneously. Meanwhile, the energy storage property possesses excellent temperature and frequency stability, and the variation of W rec and η is less than 5% within the range of 25–100 °C and 2–100 Hz. Encouragingly, superior charge-discharge performance with fast discharge speed t 0.9 of 24 ns and high power density P D of 296 MW/cm 3 is obtained. These striking comprehensive results suggest BNST-P ceramics possess potential prospects for applications.